2011
DOI: 10.1089/acm.2010.0589
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Acupressure at theSanyinjiaoPoint in the Improvement of Women's General Health

Abstract: Objectives: This study's objective was to examine the effectiveness of Sanyinjiao point (SP6) acupressure on women's general health. Design: This was a randomized, single-blind clinical trial. Setting: The setting for this trial was at Medical University, Bojnoord University of Medical Science, Bojnoord, Iran. Materials and methods: Eighty-six (86) university students were recruited for this study. Their demographic characteristics were gathered before the intervention commenced. Participants completed General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…26 27 Indeed SP6 acupressure has been considered Original paper as a self-management approach to improve women's general health. 28 EA at SP6 has been shown to improve oocyte quality and pregnancy outcome in patients with PCOS, 29 and can generate a significant analgesic effect in primary dysmenorrhoea. 30 Our experimental results also show that acupuncture (at SP6 and ST36) can significantly improve disorders of the ovarian cycle induced by continuous light exposure.…”
Section: Ea Simultaneously Improved Ovarian Cycle and Glucose Metabolismmentioning
confidence: 99%
“…26 27 Indeed SP6 acupressure has been considered Original paper as a self-management approach to improve women's general health. 28 EA at SP6 has been shown to improve oocyte quality and pregnancy outcome in patients with PCOS, 29 and can generate a significant analgesic effect in primary dysmenorrhoea. 30 Our experimental results also show that acupuncture (at SP6 and ST36) can significantly improve disorders of the ovarian cycle induced by continuous light exposure.…”
Section: Ea Simultaneously Improved Ovarian Cycle and Glucose Metabolismmentioning
confidence: 99%
“…Acupressure involves the application of pressure on the traditional acupuncture points instead of puncturing the skin, and aims to correct such imbalances. Previous studies have suggested that acupressure is an effective method for reducing stress [8]; anxiety [9]; depressive mood [10] as well as improving general health [11].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 867 articles retrieved, 33 studies [2, 435] met the inclusion criteria for the current analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Along with the development of evidence-based medicine, international clinical trials on acupuncture have been increasing in number and raising greater controversies on whether or not acupuncture is effective. While the majority of international clinical trial reports on acupuncture have demonstrated that acupuncture therapy is indeed effective, some research has shown that acupuncture therapy benefits patients, but is equivalent to the placebo effect [1], and some people consider acupuncture therapy to be ineffective [2]. Currently, it is widely believed that such a result is a product of the higher-quality methodology for international randomized controlled trials (RCTs) of acupuncture.…”
Section: Introductionmentioning
confidence: 99%